PIEZO1 is downregulated in glenohumeral chondrocytes in early cuff tear arthropathy following a massive rotator cuff tear in a mouse model - Anderson, Devon E.; Broun, Katherine G.; Kundu, Paromita; Jing, Xingyu; Tang, Xiang; Lu, Christopher; Kotelsky, Alexander; Mannava, Sandeep; Lee, Whasil (Frontiers in Bioengineering and Biotechnology, 2023)
A massive rotator cuff tear (RCT) leads to glenohumeral joint destabilization and characteristic degenerative changes, termed cuff tear arthropathy (CTA). Understanding the response of articular cartilage to a massive RCT will elucidate opportunities to promote homeostasis following restoration of joint biomechanics with rotator cuff repair. Mechanically activated calcium-permeating channels, in part, modulate the response of distal femoral chondrocytes in the knee against injurious loading and inflammation. The objective of this study was to investigate PIEZO1-mediated mechanotransduction of glenohumeral articular chondrocytes in the altered biomechanical environment following RCT to ultimately identify potential therapeutic targets to attenuate cartilage degeneration after rotator cuff repair. First, we quantified mechanical susceptibility of chondrocytes in mouse humeral head cartilage ex vivo with treatments of specific chemical agonists targeting PIEZO1 and TRPV4 channels. Second, using a massive RCT mouse model, chondrocytes were assessed for mechano-vulnerability, PIEZO1 expression, and calcium signaling activity 14-weeks post-injury, an early stage of CTA. In native humeral head chondrocytes, chemical activation of PIEZO1 (Yoda1) significantly increased chondrocyte mechanical susceptibility against impact loads, while TRPV4 activation (GSK101) significantly decreased impact-induced chondrocyte death. A massive RCT caused morphologic and histologic changes to the glenohumeral joint with decreased sphericity and characteristic bone bruising of the posterior superior quadrant of the humeral head. At early CTA, chondrocytes in RCT limbs exhibit a significantly decreased functional expression of PIEZO1 compared with uninjured or sham controls. In contrast to the hypothesis, PIEZO1 expression and activity is not increased, but rather downregulated, after massive RCT at the early stage of cuff tear arthropathy. These results may be secondary to the decreased axial loading after glenohumeral joint decoupling in RCT limbs.